PEMAHAMAN KEANEKARAGAMAN BUDAYA INDONESIA MELALUI PROYEK MINIATUR TRADISIONAL PADA PEMBELAJARAN IPS DI SEKOLAH DASAR - Anggraita, Ryanjani Lila; Ahmad Muhibbin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the implementation of project-based learning through the creation of traditional house miniatures in Social Studies learning for 4th-grade students at SDN 01 Jati, Jaten, Karanganyar. It also aims to understand how this approach helps students recognize Indonesia's cultural diversity and develop 21st-century skills, such as creativity, collaboration, problem-solving, and communication. This research employs a qualitative descriptive method with data collected through observation, interviews, and documentation. The results show that project-based learning successfully creates an active, creative, and enjoyable learning environment. Students not only gain a deeper understanding of cultural diversity but also demonstrate significant development in 21st-century skills. Although challenges such as varying student abilities and limited time were encountered, teacher strategies, such as intensive guidance and flexible time management, effectively addressed these obstacles. In conclusion, project-based learning is an effective method to enhance cultural understanding and student skills and serves as an innovative model for Social Studies learning in elementary schools.